Polar extracts from the berry-like fruits of Hypericum androsaemum L. as a promising ingredient in skin care formulations. (4th January 2017) - Antognoni, Fabiana; Lianza, Mariacaterina; Poli, Ferruccio; Buccioni, Michela; Santinelli, Claudia; Caprioli, Giovanni; Iannarelli, Romilde; Lupidi, Giulio; Damiani, Elisabetta; Beghelli, Daniela; Alunno, Alessia; Maggi, Filippo
Abstract: Ethnopharmacological relevance: The top flowering aerial parts of the Hypericum species are traditionally used to prepare ointments to heal cuts and burns. Sometimes even the fruits are used for these purposes. Hypericum androsaemum L., commonly known as tutsan or shrubby St. John's Wort, is a Mediterranean medicinal plant which has been traditionally used to prepare an ointment for treating cuts and wounds. Aim of the study: To evaluate the extracts obtained from H. androsaemum red berries as functional ingredients for skin care formulations. Materials and methods: The methanolic extract was obtained by Soxhlet extraction while the aqueous extract was prepared by decoction; their composition was determined by HPLC analysis. Their biological activities were measured in terms of proliferation and migration of human fibroblasts, inhibition of collagenase activity, and immunomodulatory effects on human peripheral blood mononuclear cells (PBMCs). In addition, we evaluated their photostability by UV spectroscopy and their protective effects against APPH-induced hemolysis in red blood cells (RBC). Results: The polar extracts contained significant amounts of shikimic (108, 143.7–115, 901.3 mg/kg) and chlorogenic acids (45, 781.1–57, 002.7 mg/kg). The main components of these extracts made an important contribution to a significant increase in human fibroblast migration. Both extracts were also active as collagenase inhibitors, with the aqueous one showing a greater inhibitory capacity (IC50 value of 88.1 µg/mL), similar to that of chlorogenic acid. The kinetic parameters determined for the enzymatic reaction revealed for both aqueous extract and chlorogenic acid an uncompetitive mechanism of inhibition. The methanolic extract showed important effects on PBMCs by modulating IL-6. Both extracts proved to be photostable in the UVA/B range and protected RBC against peroxidation at low concentrations. Conclusions: H. androsaemum red berries were proven to contain phytochemicals that improve skin regeneration, hence potentially employable in skin care formulations. Graphical abstract: